Urban planning for the city of the future : a multidisciplinary approach - Flynn, Susan; Hayes, Richard (Emerald Publishing Limited, 2023)
The lines between the fields of strategy, urban planning, architecture and sociology are currently blurred by "futurising" discourses about progress, renewal and the crises of urbanisation. Aided by an ambitious multifaceted lens, Urban Planning for the City of the Future: A Multidisciplinary Approach provides a unique glimpse into planning, growth, regeneration and demographic urgency in the light of globalisation, climate change and rapid technological change. Presenting a case study of the city of Waterford, this edited collection explores how the city of the future might be shaped. Contributors ask not only how to plan the ideal city of the future, but also how to prioritise citizens' rights, participation and engagement in that city. Offering solutions that put these rights at the heart of city life, chapters also tackle some of the modern city's crises, exploring options for the preservation, incorporation and expansion of the city's heritage, landmark buildings and unique geographical history. Bringing together multidisciplinary perspectives from strategy, urban geography, psychology, sociology, film, data and digital studies, Urban Planning for the City of the Future: A Multidisciplinary Approach builds a compelling, comprehensive, multifaceted case-study of a small, modern European city that can serve as a laboratory for future urban planning elsewhere.